Integrating Numismatic Evidence into the Study of the Urban Landscape of Paphos. From Palaepaphos to Nea Paphos with the Last King - Iacovou, Maria; Markou, Evangeline (Tekmeria, 2023)
The discovery of a bronze coin, in the context of controlled excavations conducted by the Palaepaphos Urban Landscape Project (PULP) on the plateau of Palaepaphos-Hadjiabdoullah since 2009, presented the opportunity for a challenging collaborative dialogue on the integration of numismatic discoveries, as well as relevant inscriptions and literary sources, with the current results of the landscape analysis and the excavations that have contributed to the identification of the plateau as the citadel of the polis of Paphos in the Cypro-Classical period. The identification of the coin as a bronze issue of either Timarchos (350? – 325? BC) or his son and last king of Paphos Nikokles (325? – 310/9 BC) leads first to an updated assessment of the state of research regarding the bronze coinage of the Paphian mint under its last fourth-century kings. The coin is then contextualised in the micro-environment of the recently located secular monument, a workshop complex, where it was found. A preliminary study of the ceramic material suggests that the workshop functioned contemporaneously with the palace, an architecturally impressive monument with which it shares the north side of the citadel. The precarious state of the fourth-century phase of the palatial building, which suggests that it could have lost its official status before the abolition of the Paphian dynasty (an event historically dated to 310/9 BC), turns the discussion towards Nea Paphos, where five coins of the same type were also discovered during controlled excavations. It is hereby suggested that by exploiting the results of the landscape analysis conducted by PULP, in combination with the still limited archaeological evidence, the establishment of Nea Paphos can be approached from the perspective of its predecessor, the old capital of Paphos. The possibility that a fourth-century monetized society was already residing in Nea Paphos reopens the long-debated issue of its foundation